La promoción turística y la afluencia de visitantes en el cantón Quevedo, año 2020 - Hernandez Pin, Maria Fernanda (2021)
The present research work consists of presenting a tourism promotion strategy for the influx of visitors to the Canton Quevedo, located in the province of Los Rios, whose main objective is to promote our city with quality and diversify through the natural resources or tourist attractions that we have. The research was developed with analytical and descriptive character. This research work began with the development of the theoretical foundation, for which a search of the variables in the different available sources was carried out, in order to achieve the correct definition and from there start with the development of the case. In chapter one, the proposal for a tourism promotion strategy that will improve the number of visitors to the canton is presented, which will contribute to solve the problems by means of applicable strategies that will capture the interest of national and local tourists. Chapter two contains the detected situations where the tourist places of the city and the attractions of each one are detailed, in the proposed solutions a guide with clear information for tourists was presented, as well as the conclusions and recommendations pertinent to the investigation. The purpose of this project is that tourism promotion is a contribution to tourism in the Canton Quevedo, because by promoting the sites that the Canton has in an appropriate manner, with a well-directed promotion through different media such as posters, flyers, or social networks, among others, focused on achieving an increase in the influx of visitors being the population the main beneficiary through the economic resources obtained from tourism.